REPORT ON AN OUTBREAK OF BABESIOSIS IN TELLICHERRY GOATS - T.Muthuramalingam; P.Pothiappan; P.Tensingh Gnanaraj; S. Meenakshi Sundaram; T.R. Pugazhenthi; S. Parthiban (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The prevalence of Babesia infection was studied in newly purchased Tellicherry goats from Thalasserry, Kerala State to a private goat farm at Chennai. A total number of 168 goats were examined for the presence of Babesia. The study revealed that 58 (34.5%) goats were infected with Babesia ovis. The prevalence of Babesia infection between males and females and different age groups of goats was non-significant. Infected goats showed varying clinical signs of inappetence, depression, increased respiratory rate, weakness, coughing, nasal discharge, ocular discharge, diarrhea,   body temperature ranging 39.5- 41.2oC and abortion. Blood parameters revealed decrease in total red blood cells (RBC) count, haemoglobin concentration (Hb), Volume of packed red cells (VPRC), platelets counts and increase in lymphocyte and neutrophil count.